2021
DOI: 10.1007/s12072-021-10270-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of erectile dysfunction in patients with liver cirrhosis: a systematic review and meta-analysis

Abstract: Background and aims Liver cirrhosis is associated with an increased risk of developing erectile dysfunction (ED). The aim of this systematic review and meta-analysis was to evaluate the prevalence of ED and its risk factors in male patients with liver cirrhosis. Methods A systematic search of PubMed (Medline), EMBASE, OVID Medline, the Cochrane Library, and other databases was performed for this review. Two investigators reviewed the abstracts obtained from the search and selected manuscripts for full-text rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…This result was agreed with Maimone et al who concluded that Patients with ED were signi cantly older than those without ED (p.value = 0.006) 13 The explanation for this result is morphologic and physiologic mechanisms that are involved in the aging process play a key role in the development of sexual dysfunction in the absence of any other clinical or medical condition. Also, a meta-analysis done by Yoo et al concluded that Patients with ED were 5.8 years older (p < 0.001) 14 .…”
Section: Resultsmentioning
confidence: 99%
“…This result was agreed with Maimone et al who concluded that Patients with ED were signi cantly older than those without ED (p.value = 0.006) 13 The explanation for this result is morphologic and physiologic mechanisms that are involved in the aging process play a key role in the development of sexual dysfunction in the absence of any other clinical or medical condition. Also, a meta-analysis done by Yoo et al concluded that Patients with ED were 5.8 years older (p < 0.001) 14 .…”
Section: Resultsmentioning
confidence: 99%
“…However, we want to emphasize that frequently sexual function and ED, in particular, are often poorly investigated, if not ignored, in the vast majority of cases. Some evidence indicates that an improvement of sexual function can ameliorate couple intimacy quality, and quality of life, as well as diseases-related distress [ 22 , 23 , 28 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Systemic diseases characterized by organ failure (such as end-stage renal diseases [22] and liver cirrhosis [23], as well as those conditions related to systemic inflammation such as HIV infection [24,25] or to some rheumatic and/or autoimmune diseases [26][27][28][29]) are frequently associated with ED, couple impairment and reduced quality of life. Similarly, considerations can be drawn for some malignancies with long life expectancy such as lymphomas and testis cancers [30].…”
Section: Evidence and Remarksmentioning
confidence: 99%
“…At present, some scholars consider that there is a correlation between cirrhosis and ED, which can be explained by haemodynamic alteration, hypogonadism, hypotestosteronemia, unhealthy lifestyle, and a lower quality of life. Through meta-analysis, Yoo et al (17) found that the prevalence of ED in cirrhotic patients was 79.08%, and in decompensated cirrhotic patients was 88.4%. After controlling for other conditions such as diabetes, alcoholism, severe cardiac conditions, etc., Paternostro et al (18) discovered that among male cirrhotic patients, 55% were categorized as mild-to-moderate ED and 8.3% as moderate-to-severe ED, and that with the decline of liver function, the severity of ED increased and the IIEF-5 score decreased significantly.…”
Section: Epidemiology Of Ed In Cldsmentioning
confidence: 99%
“…Bioavailable testosterone includes albumin-bound testosterone and free testosterone. According to a meta-analysis, free testosterone levels were significantly lower in ED patients than in the non-ED group (17). Patients with hepatic insufficiency frequently have higher levels of estrogen and lower levels of testosterone, which can result in an increase in the production of sex hormone-binding globulin through a negative feedback loop.…”
Section: Mechanisms Of Clds Related Ed Gonadal Dysfunctionmentioning
confidence: 99%